RANCANG BANGUN SISTEM TANAMAN HIDROPONIK JENIS IPOMOEA AQUATICA DENGAN INTENSITAS CAHAYA LAMPU BERBASIS IOT - Hartono, Elvianto Dwi; Ikhlasul Nusa (Jurnal Fakultas Teknologi Informasi, 2023)
Plants have the ability to create their own food through the use of chlorophyll in the process of photosynthesis. The benefits that we can take advantage of from a plant are as herbal medicine, food ingredients, and can also produce oxygen which is useful for the survival of mankind. The purpose of this study was to design a tool for providing nutrition to hydroponic plants using catfish manure, to design a tool to cut plants in an automatic way, and to design a tool to replace sunlight for plants that can photosynthesize. This designed tool is based on the Arduino microcontroller. For automatic cutting, the HC-SR04 sensor will be used to determine the height of the plant with the help of a dc motor for the cutter and a stepper motor to drive the sensor.